Inactivation of Shiga toxin-producing Escherichia coli in fresh beef by electrolytically-generated hypochlorous acid, peroxyacetic acid, lactic acid and caprylic acid - Cap, Mariana; Vaudagna, Sergio Ramon; Mozgovoj, Marina Valeria; Soteras, Trinidad; Sucari, Adriana; Signorini, Marcelo; Leotta, Gerardo (Elsevier, 2019)
Several studies have been conducted to verify the decontamination potential of electrolyticallygenerated hypochlorous acid, peroxyacetic acid, lactic acid and caprylic acid against Shiga toxin-producing Escherichia coli (STEC) in beef products. However, there is no consensus regarding their effectiveness. The aim of this study was to compare these four treatments under the same conditions and establish a ranking according to their effectiveness to inactivate STEC in fresh beef. Samples were inoculated with two levels of inoculum and rinsed for 15 s in 100 ml of antimicrobial solution treatment. Caprylic acid was the most effective treatment, followed by lactic acid and peroxyacetic acid. Electrolytically-generated hypochlorous acid had no effect. Sensory analysis showed no significant differences either in flavor or in color between samples treated with caprylic acid and reference samples. Caprylic acid appears to be an effective and viable alternative to conventional interventions frequently used for meat product decontamination.